Isoxazol-5(2H)-one: a new scaffold for potent human neutrophil elastase (HNE) inhibitors - Claudia Vergelli; Igor A. Schepetkin; Letizia Crocetti; Antonella Iacovone; Maria Paola Giovannoni; Gabriella Guerrini; Andrei I. Khlebnikov; Samuele Ciattini; Giovanna Ciciani; Mark T. Quinn (Taylor & Francis Group, 2017)
Human neutrophil elastase (HNE) is an important target for the development of novel and selective inhibitors to treat inflammatory diseases, especially pulmonary pathologies. Here, we report the synthesis, structure-activity relationship analysis, and biological evaluation of a new series of HNE inhibitors with an isoxazol-5(2H)-one scaffold. The most potent compound (2o) had a good balance between HNE inhibitory activity (IC50 value =20 nM) and chemical stability in aqueous buffer (t1/2=8.9 h). Analysis of reaction kinetics revealed that the most potent isoxazolone derivatives were reversible competitive inhibitors of HNE. Furthermore, since compounds 2o and 2s contain two carbonyl groups (2-N-CO and 5-CO) as possible points of attack for Ser195, the amino acid of the active site responsible for the nucleophilic attack, docking studies allowed us to clarify the different roles played by these groups.